Fusi Protoplas Interspesies Chlorella pyrenoidosa dan Dunaliella salina - Yunanto, Yudi; Kusumaningrum, Hermin Pancasakti; Pujiyanto, Sri (JURNAL SAINS DAN MATEMATIKA, 2013)
Microalgae Chlorella pyrenoidosa and Dunaliella salina have been used as natural aquaculture food supplement because the previous contains 60,5% proteins and 180,8 mg/100g β-carotene and the other  were accumulated β-carotene by 95% from their total carotenoid.  Carotenoid  production can be improved by protoplast fusion technique. The aim of the research was conducted protoplast fusion of from C. pyrenoidosa and D. salina in order to gaining boarder salinity spectrum for natural aquaculture food supplement . The research metodology consist of protoplast  isolation followed by protoplast fusion process  induced by PEG6000 and regeneration of  fusant.  Protoplast fusion was done in three different PEG incubation time that are 15, 30 and 45 minutes.  The fusants were grown in 2 different medium, sea water media and fresh water media.  Research result shows that optimal fusion incubation time with PEG6000 is at 30 minutes.  Fusant can grown in both  medium and revealed higher β-carotene contents 2,008 µg/ml comparing with their parents.   Keywords: Protoplast fusion, Chlorella pyrenoidosa, Dunaliella salina, β-carotene.